Kava Hangover and Gold-standard Science - Aporosa, S. (Apo); Tomlinson, Matt (Anthropologica, 2014)
Kava, a beverage drunk in much of the South Pacific, is both celebrated and controversial. It is often considered an emblem of traditional indigenous practice but also criticized for its physical effects on heavy drinkers. This article reports the results of a study wherein tests were administered to schoolteachers in Fiji to measure effects of the previous night's drinking. The tests revealed that kava intoxication seems to affect processing speed but not working memory. The authors caution that the results must be balanced by acknowledgement of kava's role in bringing communities together in support of institutions such as schools.